Limelight - Benjamin, Walter (Kobenhavn : Udstillingsbygningen ved Charlottenborg, 1986)
Bonde, Peter ; Brecht, George ; Broager, Ole ; Byars, James Lee ; Carstensen, Claus ; Reuter Christiansen, Ursula ; Droese, Felix ; Frandsen, Erik A. ; Hoyer Hansen, Lone ; Have, Henrik ; Höckelmann, Antonius ; Jensen, Berti ; Kiecol, Hubert ; Klossowski, Pierre ; Kvium, Michael ; Langkilde, Kirsten ; Lemmerz, Christian ; Merz, Mario ; Norgard; Lars ; Palermo, Blinky ; Pedersen, Poul ; Ravn, Lars
Limelight, Udstillingsbygningen ved Charlottenborg, Kobenhavn, 8 juni - 20 juli 1986
boek